Genetic variants of CTLA4 are associated with clinical outcome of patients with multiple myeloma - Gonzalez-Montes, Yolanda; Rodriguez-Romanos, Rocío; Villavicencio, Alicia; Osca-Gelis, Gemma; González-Bártulos, Marta; Llopis, Francesca; Clapes, Victòria; Oriol, Albert; Sureda, Anna; Escoda, Lourdes; Sarrà, Josep; Garzó, Ana; et al. (Frontiers in Immunology, 2023)
Immune dysfunction in patients with multiple myeloma (MM) affects both the innate and adaptive immune system. Molecules involved in the immune checkpoint pathways are essential to determine the ability of cancer cells to escape from the immune system surveillance. However, few data are available concerning the role of these molecules in predicting the kinetics of progression of MM. We retrospectively analysed polymorphisms of CTLA4 (rs231775 and rs733618), BTLA (rs9288953), CD28 (rs3116496), PD-1 (rs36084323 and rs11568821) and LAG-3 (rs870849) genes in 239 patients with newly diagnosed MM. Patients with a CTLA4 rs231775 AA/AG genotype showed a median progression-free survival (PFS) significantly lower than those with GG genotype (32.3 months versus 96.8 months respectively; p: 0.008). The 5-year PFS rate was 25% for patients with grouped AA and AG genotype vs 55.4 % for patients with GG genotype. Multivariate analysis confirmed the CTLA4 rs231775 genotype as an independent risk factor for PFS (Hazard Ratio (HR): 2.05; 95% CI: 1.0-6.2; p: 0.047). Our results suggest that the CTLA4 genotype may identify patients with earlier progression of MM. This polymorphism could potentially be used as a prognostic biomarker.